Field reports form for submitting seasonal observations of Iowa birds and photograph of a Snowy Owl, Jack Jones, fall 1987 - Jones, Jacket al (1987)
Fall report of birds found in northwest Iowa contributed by Jack Jones. The report also includes a newspaper clipping with a photograph of Snowy Owl. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1987. This document is related to a letter from Randall D. Williams that describes a Snowy Owl sighting: https://avian.lib.iastate.edu/documents/4032/view Epson - sheet feed/flatbed